Pengaruh Likuiditas, Struktur Modal, Profitabilitas, Kebijakan Dividen dan Ukuran Perusahaan Terhadap Nilai Perusahaan Pada Perusahaan Properti dan Real Estate yang Terdaftar di Bursa Efek Indonesia Tahun 2015-2019 - Agatha, Nike Aprilya; Irsad, Moch (Jurnal Ilmiah Akuntansi dan Humanika, 2021)
The purpose of this study was to examine the effect of liquidity, capital structure, profitability, dividendJpolicy, and company size on firmvalue. Firm value is an indicator of financial performance for companies that go public. high company value will indicate highshareholder prosperity. This research was conducted on property and real estate companies listed on the Indonesia Stock Exchange(BEI)J2015-2019. The number of samples taken was 24 companies. The sampling method in this study using purposive sampling andusing multiple linear regression analysis techniques assisted by the SPSS program which includes classical assumption test and partial test (t-test) with a real level (α)Jof 05%. The results of this study indicate that liquidity and capital structure have a negative effect onFirm Value, and for Profitability, Dividend Policy, and Firm Size have positive effect on Firm Value.